The organization of R&D activities : a study of MNC subsidiaries in the electronics industry in Singapore - Lee, Michelle Hui Lin (2008)
An exploratory study to identify the various working relationships that a Research and Development (R&D) subsidiary of Multinational Corporations(MNC) has to deal with.